NILAI TAMBAH (VALUE ADDED) PELAKU PASAR DALAM RANTAI PASOK AYAM BROILER DI KOTA KUPANG - Adun, Yeremias; Krova, Maria; Lole, Ulrikus R.; Sogen, Johanes G. (Jurnal Sain Peternakan Indonesia, 2024)
A survey was conducted in Kota Kupang to analyze the added value and factors influencing the added value obtained by broiler breeders and traders in Kota Kupang. The sampling methods were used in three stages, namely: first, the market determination was used using the census method; second, sample traders used a non-proportional random method; and sample farmers used the method of snowball sampling. The sample in this study was 25 respondents from breeders and 25 from traders. Data collection was carried out through observation, interviews, and documentation. The data analysis methods used are value-added analysis and linear multiple regression analysis. The research results show that the added value obtained by broiler chicken breeders in Kota Kupang is IDR 1,518.00/kg live weight, and broiler chicken traders are IDR 18,053.00/kg live weight. The conversion factor for breeders is IDR 1,620, and for traders, IDR 5,333. The statistical difference test results show no significant difference between the added value obtained by breeders and traders of broiler chickens in Kota Kupang. Linear multiple analysis shows that at the farmer's acquisition level, the factors influencing added value are the number of broiler chickens and production costs. At the broiler chicken trader level, the selling price of broiler chickens, the number of broiler chickens and production costs have no significant effect on the added value obtained.